Wheel access has opposing effects on stress physiology depending on social environment in female prairie voles (Microtus ochrogaster). (4th March 2019) - Jarcho, Michael R.; McNeal, Neal; Colburn, William; Normann, Marigny C.; Watanasriyakul, W. Tang; Grippo, Angela J.
Abstract: Physical exercise and chronic social stress are both known to impact general health and hypothalamic-pituitary-adrenal (HPA) axis function, albeit typically in opposing directions. Therefore, the question we investigated in this study was how these two factors – physical exercise and chronic social isolation – would interact when presented simultaneously in a female rodent model. Adult female prairie voles were separated into four experimental groups: (1) isolated without wheel access, (2) isolated with wheel access, (3) paired without wheel access, and (4) paired with wheel access. Plasma, hair, and adrenal glands were sampled to investigate changes in stress physiology. Our results indicate that, when isolated, wheel access had a mitigating effect on HPA activity. However, in paired animals, wheel access had the opposite effect, as both adrenal mass and increase in hair corticosterone concentrations were greater in paired animals with wheel access. Strong correlations were detected between change in hair corticosterone and adrenal mass, while no correlations were found between plasma corticosterone and either of the other markers. These results imply that the HPA axis is highly sensitive to both the social environment and the physical demands placed on the individual, and that when investigating the effects of chronic isolation, both hair corticosterone and adrenal mass may be more reliable markers than a single plasma corticosterone sample.